2017
DOI: 10.1002/ijgo.12325
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic injury and patient displacement in gynecologic laparoscopic surgery using a beanbag and shoulder supports

Abstract: Objective: To quantify the incidence of peripheral neuropathy in gynecologic laparoscopic surgery using a combination of beanbag, eggcrate foam, and shoulder supports; and to assess patient displacement during surgery in a steep Trendelenburg position and determine variables correlated with displacement. Methods Conclusion:Use of beanbags with shoulder supports and convoluted foam armboard pads was associated with minimal patient displacement and risk of arm and leg neurologic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Removing the small intestine from the pelvic cavity is important to obtain a clear view and to avoid inadvertent contact with the intestine during surgery. However, the steep Trendelenburg position has been reported to be associated with complications such as gas embolism, 1 increased intraocular pressure, [2][3][4] increased intracranial pressure, 5,6 decreased blood flow in the internal carotid artery, 7 spontaneous otorrhea, 8 upper-body complications, 9 nerve injury, 10,11 peripheral neuropathy, 12 venous thromboembolism, 13,14 and lower-extremity compartment syndrome caused by impaired blood flow. 15 Gould et al previously reported that a mean Trendelenburg angle of 28.0 was required to complete robotic gynecologic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Removing the small intestine from the pelvic cavity is important to obtain a clear view and to avoid inadvertent contact with the intestine during surgery. However, the steep Trendelenburg position has been reported to be associated with complications such as gas embolism, 1 increased intraocular pressure, [2][3][4] increased intracranial pressure, 5,6 decreased blood flow in the internal carotid artery, 7 spontaneous otorrhea, 8 upper-body complications, 9 nerve injury, 10,11 peripheral neuropathy, 12 venous thromboembolism, 13,14 and lower-extremity compartment syndrome caused by impaired blood flow. 15 Gould et al previously reported that a mean Trendelenburg angle of 28.0 was required to complete robotic gynecologic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Temimi et al (2017) mentioned that the Trendelenburg position may increase the risk of upper limb neuropathy. In our review of the literature, only two studies were found that measured the time spent in this position (Klauschie et al, 2010; Treszezamsky et al, 2017). Both studies concluded that patient displacement on the surgical table was not influenced by the time in the Trendelenburg position and that this factor was not identified as a risk factor for the development of PNI.…”
Section: Discussionmentioning
confidence: 99%
“…Data were gathered preoperatively on patient-related variables (Abdalmageed et al, 2017;Al-Temimi et al, 2017;Welch, 2017), including age, gender, perioperative American Society of Anesthesiologists risk, BMI, specialty in charge, and category of diagnosis. Data were gathered intraoperatively on perioperative variables, including type of intervention, the use of conventional compression stockings or intermittent pneumatic compression (Güzelküçük et al, 2014;Kim et al, 2016), the use of Allen shoulder supports, total duration of the surgical intervention, and time in minutes (Bohrer et al, 2009) spent in the Trendelenburg position (Treszezamsky et al, 2017) and in the left or right lateral positions.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that intraocular pressure increases in steep Trendelenburg resulting in the potential for ocular complications such as corneal abrasion and ischemic optic neuropathy [32][33][34]. Intraoperative peripheral nerve injuries are rare, but occasionally serious when related to lithotomy positioning with steep Trendelenburg [35][36][37]. Therefore, instead of using constant steep TIA and high PP pairs in laparoscopic procedures, they should be adjusted individually for each case to an extent where the operative field is adequate to proceed safely with the planned operation.…”
Section: An Objective Visual Indexing Based On Anatomical Landmarksmentioning
confidence: 99%